2016
DOI: 10.4236/ajps.2016.710139
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and Correlation among Sugarcane (<i>Saccharum</i> spp.) Yield and Some Agronomic and Sugar Quality Traits in Ethiopia

Abstract: To assess broad sense heritability and phenotypic and genetic correlations among sugarcane yield components, an experiment was conducted at Wonji and Metehara Sugar Estates of Sugar Corporation of Ethiopia during 2012/2013. High broad sense heritability (h 2 ) was detected for stalk diameter (0.730), single cane weight (0.672), millable cane number (0.624), stalk height (0.624) and pol % (0.608), indicating that these traits could be selected for easily. Expected genetic gain of the yield components was modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 16 publications
(27 reference statements)
6
19
0
1
Order By: Relevance
“…Similar result were also reported by Tena et al, (2016), They found high broad sense heritability for stalk diameter, single cane weight, millable cane weight, stalk height and pol %. Gowda et al, (2016) reported that cane yield components viz., sugar yield number of millable cane, single cane weight and cane yield showed high heritability but Their result is slightly different for plant height, stalk diameter, brix percentage pol percentage, purity percentage and CCS percentage, This different might be due to environmental variations in expression of these traits.…”
Section: Resultssupporting
confidence: 90%
“…Similar result were also reported by Tena et al, (2016), They found high broad sense heritability for stalk diameter, single cane weight, millable cane weight, stalk height and pol %. Gowda et al, (2016) reported that cane yield components viz., sugar yield number of millable cane, single cane weight and cane yield showed high heritability but Their result is slightly different for plant height, stalk diameter, brix percentage pol percentage, purity percentage and CCS percentage, This different might be due to environmental variations in expression of these traits.…”
Section: Resultssupporting
confidence: 90%
“…Variance components were estimated for each of the sources of variation in the model. Broad-sense heritability (H 2 ) on an individual plant basis was calculated using the variance components based on following the equation (Gusmini & Wehner, 2004;Tena, Mekbib, & Ayana, 2016):…”
Section: Discussionmentioning
confidence: 99%
“…Variance components were estimated for each of the sources of variation in the model. Broad‐sense heritability ( H 2 ) on an individual plant basis was calculated using the variance components based on following the equation (Gusmini & Wehner, ; Tena, Mekbib, & Ayana, ):H2=σG2σP2=σG2σnormalG2+σnormalE2where σG2 is the total genetic variance, σP2 is the total phenotypic variance, and σE2 is the environmental variance. In this case, σG2 represents the variation among miscane progeny genotypes, and σG2 represents the interaction between genotype and block.…”
Section: Methodsmentioning
confidence: 99%
“…Chandrakant (2007) revealed that number of shoots at 120 DAP, number of millable cane at harvest and single cane weight were had consistent trend of significant association with cane yield. Kang et al, (1983), Sreekumar et al, (1994), Tena et al, (2016), Thangavelu (2011) and Thippeswamy et al, (2003).…”
Section: Association Of Cane Yield With Other Characters In Sugarcanementioning
confidence: 98%
“…Sanghera et al, (2015) reported significant and positive correlation of cane yield with number of millable cane at 10 months, stalk length, single cane weight, cane diameter and germination percentage at 45 DAP indicating the importance of these traits to be involved in selection criteria. Tena et al, (2016) reported that cane yield showed strong positive and highly significant correlation with number of millable cane, single cane weight, stalk height and sugar yield. Tadesse et al, (2014) found that cane yield was positively and highly significantly correlated with single cane weight and number of millable cane while positive and significantly correlated with cane diameter.…”
Section: Association Of Cane Yield With Other Characters In Sugarcanementioning
confidence: 99%